2013
DOI: 10.1186/1471-2229-13-11
|View full text |Cite
|
Sign up to set email alerts
|

Development of genomic SSR markers for fingerprinting lettuce (Lactuca sativa L.) cultivars and mapping genes

Abstract: BackgroundLettuce (Lactuca sativa L.) is the major crop from the group of leafy vegetables. Several types of molecular markers were developed that are effectively used in lettuce breeding and genetic studies. However only a very limited number of microsattelite-based markers are publicly available. We have employed the method of enriched microsatellite libraries to develop 97 genomic SSR markers.ResultsTesting of newly developed markers on a set of 36 Lactuca accession (33 L. sativa, and one of each L. serriol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 35 publications
5
34
1
3
Order By: Relevance
“…Interestingly, our data are consistent with previous studies in faba bean which revealed a larger genetic variation and differentiation within than between population (Terzopoulos and Bebeli 2008; Ouji et al 2011;Oliveira et al 2016). Moreover, this was consistent with the findings from other species such as grapevine (De Andrés et al 2012), olive (Belaj et al 2007), apple ) and lettuce (Rauscher and Simko 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, our data are consistent with previous studies in faba bean which revealed a larger genetic variation and differentiation within than between population (Terzopoulos and Bebeli 2008; Ouji et al 2011;Oliveira et al 2016). Moreover, this was consistent with the findings from other species such as grapevine (De Andrés et al 2012), olive (Belaj et al 2007), apple ) and lettuce (Rauscher and Simko 2013).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the mean value of PIC (0.63) was less than that (0.67) previously reported for genomic-SSRs (Jiao et al, 2012), but significantly higher than the figure (0.44) for EST-SSRs (Zhang et al, 2012). Our results are in agreement with that reported in lettuce (Rauscher and Simko, 2013). Compared with ESTSSRs, genomic-SSRs have relatively high polymorphism and good genome coverage, so they can be used in constructing a linkage map.…”
Section: Ssr Polymorphismsupporting
confidence: 87%
“…This result was higher than 0.32 reported by [10] but lower than 0.55 of [19] and 0.56 of [20]. This may be mainly due to genetic background of tested cultivars and chromosome loci linked to SSR marker.…”
Section: Est-ssr Polymorphisms In Lettucecontrasting
confidence: 67%